The adventures of the mountain men : true tales of hunting, trapping, fighting, adventure, and survival - Brennan, Stephen Vincent (Skyhorse Publishing, 2017)
A collection of anecdotes about hunting, trapping, and exploring in the Rocky Mountains in the first half of the nineteenth century.